The Impact of Hot Air Drying on the Physical‐Chemical Characteristics, Bioactive Compounds and Antioxidant Activity of Acerola (Malphigia emarginata) Residue. Issue 2 (21st January 2014) - Nóbrega, Erly M.; Oliveira, Edson L.; Genovese, Maria I.; Correia, Roberta T.P.
Abstract This article evaluates the effect of hot air drying on the physicochemical characteristics, color, concentration of bioactive compounds and antioxidant activity of agroindustrial residue of acerola, which was hot air dried under different conditions of temperature (60, 70 and 80C) and air velocity (4, 5 and 6 m/s), taking up the residue in natura as the control group. The experimental dimensionless moisture content as a function of drying time of acerola residue is also presented and discussed. The retention values of total phenolic (26–31%), carotenoids (50–61%), anthocyanins (23–36%), proanthocyanidins (21%), ascorbic acid (40–70%) and the antioxidant activity measured by 2, 2‐diphenyl‐1‐picrylhydrazyl method (20%) were calculated and discussed. Considering the concentration of bioactive compounds detected in the final product, as well as the microbiological stability achieved by the substantial moisture reduction, it can be concluded that the dried acerola residue is an important source of bioactive compounds with appropriate characteristics to be utilized as a health‐relevant food ingredient. Practical Applications Brazil is one of the largest agricultural producers in the world. In recent years, the processing industry has developed and as a consequence, the generation of residues has also increased. The search for answers to this technological challenge was the motivation of this research, which evaluated the drying process as means for obtaining a natural functional powder from acerola residue. The data shown would provide the scientific rationale for a better exploitation of this tropical fruit residue.